2015
DOI: 10.1124/dmd.115.067876
|View full text |Cite
|
Sign up to set email alerts
|

Novel Cytochrome P450 Reaction Phenotyping for Low-Clearance Compounds Using the Hepatocyte Relay Method

Abstract: A novel cytochrome P450 (P450) reaction phenotyping method for low-clearance compounds has been developed for eight P450 enzymes (CYP1A2, 2B6, 2D6, 2C8, 2C9, 2C19, 3A, and 3A4) and pan-cytochrome using the hepatocyte relay approach. Selective mechanism-based inhibitors were used to inactivate the individual P450 enzymes during preincubation, and inactivators were removed from the incubation before adding substrates to minimize reversible inhibition and maximize inhibitor specificity. The inhibitors were quite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 25 publications
3
38
0
Order By: Relevance
“…Accordingly, these questions should be addressed by the malaria community using the various malaria animal models and controlled human clinical trials. Recent advances in in vitro drug metabolism and malaria infection models will hopefully allow for more complete and expedited investigations of such questions (Furuya, Sa, Chitnis, Wellems, & Stedman, 2014;Ng, et al, 2015;Yang, Atkinson, & Di, 2015).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Accordingly, these questions should be addressed by the malaria community using the various malaria animal models and controlled human clinical trials. Recent advances in in vitro drug metabolism and malaria infection models will hopefully allow for more complete and expedited investigations of such questions (Furuya, Sa, Chitnis, Wellems, & Stedman, 2014;Ng, et al, 2015;Yang, Atkinson, & Di, 2015).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Similarly, commonly used CYP2D6 inactivators (e.g. paroxetine) also demonstrate inhibition of CYP2B6 (Yang et al, ). If both CYP2B6 and CYP2D6 contribute to the clearance of a compound, it will be difficult to discern the f m between the two enzymes due to the inhibitor cross‐talk.…”
Section: Introductionmentioning
confidence: 98%
“…If there is cross‐talk of inhibitors among multiple enzymes, it will be challenging to estimate accurately f m and an over‐estimation of f m is likely. Typically, irreversible inhibitors are preferred over reversible inhibitors for reaction phenotyping to provide maximal knock‐out of the enzymes and to avoid the impact of inhibitor depletion during the long incubation for low clearance substrates (Yang, Atkinson, & Di, ), as the number of low clearance compounds continues to increase in drug discovery in order to achieve low doses and long half‐lives (Di et al, ; Di et al, ; Di & Obach, ). Although relatively selective inhibitors of many CYP enzymes are available (Bohnert et al, ; Di, ; Zientek & Youdim, ), the identification of CYP2B6‐specific inhibitors for reaction phenotyping has been challenging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, approaches including the hepatocyte relay method ) and coculture models, such as HepatoPac or Hurel (Chan et al, 2013), have been evaluated and have shown promising results to better determine CL int via increasing the amount of substrate depletion or metabolite formation. Although these systems have gained considerable popularity in generating metabolites and determining intrinsic clearance of very low clearance compounds, the use of these models for phenotyping studies is under development (Yang et al, 2016).…”
Section: Special Considerations: Low Turnover Extrahepatic Metabolismentioning
confidence: 99%